Applying IEEE 802.11e for Real-Time Services - Kajackas, A.; Vindašius, A. (Elektronika ir Elektrotechnika, 2009)
Analysis of IEEE 802.11e amendment and application for real time services is presented. Contention free access provided by HCCA mechanism offers QoS guarantees for latency sensitive flows. The admission algorithm is more suitable for constant bit rate traffic. The simulations show, that number of VBR VoIP sessions in wireless channel can be increased by using Traffic Stream aggregation and flexible admission control. The results are compared to ones obtained from simulations of legacy PCF. Ill. 7, bibl. 10 (in English; summaries in English, Russian and Lithuanian).